2013
DOI: 10.1021/ef401898e
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Mechanism of Corrosion in Crude Oil: A Study Using Vibrational Spectroscopic Techniques at Elevated Temperatures

Abstract: Naphthenic acid, a significant cause of corrosion of carbon-steel in crude oil, has been investigated at elevated temperatures using vibrational spectroscopic methods (Raman and Fourier transform infrared (FT-IR)). Unlike earlier reports of studies at ambient temperatures, these elevated temperature experiments performed on a series of carboxylic acids having structures similar to naphthenic acid components in crude oil and on a commercial naphthenic acid mixture show a progressive increase with increasing tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…14 Fourier transform infrared spectroscopy (FTIR) studies were performed using the same method as reported in previous papers. 8,12 Additional experiments were conducted to determine the NA corrosion behavior of bulk samples that were stripped of their surface oxides in situ. The tests were conducted on macro-sized samples and the extent of corrosion was investigated by observations in a SEM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Fourier transform infrared spectroscopy (FTIR) studies were performed using the same method as reported in previous papers. 8,12 Additional experiments were conducted to determine the NA corrosion behavior of bulk samples that were stripped of their surface oxides in situ. The tests were conducted on macro-sized samples and the extent of corrosion was investigated by observations in a SEM.…”
Section: Methodsmentioning
confidence: 99%
“…The rapid decrease in corrosion rate with time was a result of depletion of acid from the solution, as was indicated by FTIR measurements of the test solution taken after completion of the experiment. 12 The zinc surface, shown in Figure 10, displayed evidence of uniform corrosion.…”
Section: Zincmentioning
confidence: 99%
See 1 more Smart Citation
“…3. NA corrosion mechanism proposed by Chakravarti et al [28]. The mechanism shows that under high temperature conditions, NA multimers may dissociate and complex with metal ions present at the water-metal interface.…”
Section: Corrosivitymentioning
confidence: 99%
“…3) [28]. Three types of complexation have been proposed: bidentate bridging, bidentate chelate, and monodentate.…”
Section: Corrosivitymentioning
confidence: 99%